PEMBERDАYААN PEREMPUАN DESА MELАLUI KELOMPOK WАNITА TАNI LESTАRI DАLАM MENGELOLА KOMODITАS UNGGUL DI DESА SUNGАI RINGIN KАBUPАTEN SEKАDАU KАLIMАNTАN BАRАT - Samsul Ode; Erma Dwiningsih; Hendra Wijayanto; Surya Yudha Regif (Administratio, 2022)
This study aims to determine the implementation of village women's empowerment through the Women Farmers Lestari Group in managing superior commodities in Sungai Ringin Village, Sekadau Regency, West Kalimantan. Women Farmers Sustainable Village Sungai Ringin Village which focuses on managing village agricultural commodities. The type of research used is descriptive research with qualitative methods. The data collection used was observation at the Women Farmers Lestari Group, interviews with the main information, and supplementary with complete documentation in the field and analyzed through the theory of empowerment principles, namely volunteerism, autonomy, independence, participatory, egalitarian, democracy, openness, togetherness, accountability, decentralization. The results showed that from the analysis of the principles of empowerment the women farmer group had been able to implement the 10 principles of empowerment. Although the implementation of empowerment can be stopped because there are activities that are characteristic of the community in the best management of commodities, such as what is known as the rice planting season, which are carried out collectively in January-March to meet the needs of the household season. Meanwhile, the empowerment of the second superior commodity that is being initiated can be carried out outside the "pogi season" namely vegetable commodities to be marketed. Supporting factors are Government, Natural Resources, and Human Resources. While the Inhibiting Factors are internal groups related to management and membership to the influence of plant pests and changes in seasons (climate).